ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH MENABUNG DI BANK BCA KOTA MEDAN (STUDI KASUS ETNIS CINA) - Monang Ranto Tambunan; Inggrita Gusti Sari Nasution (Departemen Ekonomi Pembangunan USU, 2013)
This study entitled “Anaysis of Factors Influencing Decisions Customers Saving in BCA Medan (Ethnic Chinese Case Study)”. This study aimed to investigate the efeect of factors consisting Of products, services, promotions, location and credibility of the decisions of Chinese customers saving in BCA Medan.The analytical method used is descriptive analysis and statistical methods used multiple linear regression tool, significant testing and simultaneous testing of significant partial. Data processed using SPSS17.0 for windows. The data used are primary and secondary data.Based ond estimation/regression showed that the variables of the products, service, and the credibility has positive and significant impact in cutomers decision ethnic Chinese saving in BCA Medan alpha level of 5%, while variable promotion and location only positive influence customers decisions ethnic Chinese saving in BCA Medan. Keywords: Products, Services, Promotion, Location, Credibility and Customers Decision